2019
DOI: 10.1039/c8sm02294a
|View full text |Cite
|
Sign up to set email alerts
|

A mesoscale study of creep in a microgel using the acoustic radiation force

Abstract: We study the motion of a sphere of diameter 330 µm embedded in a Carbopol microgel under the effect of the acoustic radiation pressure exerted by a focused ultrasonic field. The sphere motion within the microgel is tracked using videomicroscopy and compared to conventional creep and recovery measurements performed with a rheometer. We find that under moderate ultrasonic intensities, the sphere creeps as a power law of time with an exponent α 0.2 that is significantly smaller than the one inferred from global c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 114 publications
(150 reference statements)
1
5
0
Order By: Relevance
“…Creep is however usually associated to irreversible strain and a non-linear stress-strain relation in bulk rheology experiments, both of which are not observed here. Interestingly, fully reversible creep motion up to the yield point has been reported in experiments in which acoustic radiation forces are used to push small spheres [50]. The relatively small pressure gradients applied in our experiments according to Equation ( 11) then cannot alone initiate bubble rise.…”
Section: Linear Response To Bjerknes Forcessupporting
confidence: 51%
See 1 more Smart Citation
“…Creep is however usually associated to irreversible strain and a non-linear stress-strain relation in bulk rheology experiments, both of which are not observed here. Interestingly, fully reversible creep motion up to the yield point has been reported in experiments in which acoustic radiation forces are used to push small spheres [50]. The relatively small pressure gradients applied in our experiments according to Equation ( 11) then cannot alone initiate bubble rise.…”
Section: Linear Response To Bjerknes Forcessupporting
confidence: 51%
“…We have used in Section IV C the constant (or zero-frequency) part of the acoustic radiation forces -the Bjerknes forcesto perform an equivalent of step-stress tests, but at a local scale R 0 and on a relatively short timescale N/ f 0.05 s. For moderate acoustic stresses σ ac ≤ σ Y , we measure a linear strain-stress relation at the end of oscillations, from which we deduce an independent measurement of the local linear elastic modulus of the fluid below yielding, G = 44.4 ± 3.5 Pa, comparable to that obtained using bulk rheology, G = 36 Pa. All quantities used to derive G are either directly measured or estimated from the resonance curve: hence, in contrast with previous works [50], our measurement is truly independent from bulk rheology. The complex time dependence of the displacement shown in Figure 4(a) is reminiscent of creep behaviour [5].…”
Section: Linear Response To Bjerknes Forcesmentioning
confidence: 96%
“…Interestingly, fully reversible creep motion up to the yield point has also been reported in experiments in which acoustic radiation forces are used to push small spheres. 53 The relatively small pressure gradients applied in our experiments according to eqn (11) then cannot alone initiate bubble rise. Performing experiments of longer duration may reveal whether the response to acoustic radiation forces indeed follows a power law or an exponential profile with time, which could be helpful to validate the recent, advanced models of yield-stress fluids.…”
Section: Linear Response To Bjerknes Forcesmentioning
confidence: 82%
“…We have used in Section 4.3 the constant (or zero-frequency) part of the acoustic radiation force to perform an equivalent of step-stress tests, but at a local scale R 0 . For moderate acoustic stresses s ac r s Y , we measure a linear strain-stress relation at the end of oscillations, from which we deduce an independent measurement of the local linear elastic modulus of the fluid below yielding, G = 44.4 AE 3.5 Pa, comparable to that obtained using bulk rheology, G = 36 Pa. All quantities used to derive G are either directly measured or estimated from the resonance curve: hence, in contrast with previous works, 53 our measurement is truly independent from bulk rheology.…”
Section: Linear Response To Bjerknes Forcesmentioning
confidence: 98%
“…Smart fluids, on the other hand, are classified into different categories according to their stimuli and responses. So far, various types of smart materials such as electrorheological fluids (ERF) (Dong et al, 2019;Liu and Choi, 2012b;Wen et al, 2008), magnetorheological fluids (MRF) (Phule, 1999;Rodrı´guez-Arco et al, 2013;Ronzova et al, 2021), ferrofluids (FFs) (Li et al, 2018(Li et al, , 2019(Li et al, , 2020Rodrı´guez-Arco et al, 2014;Usadel et al, 2019), magnetorheological gel (MRG) (An et al, 2010;Lidon et al, 2019;Pang et al, 2020), magnetorheological foam (Makarova et al, 2019;Muhazeli et al, 2021), and magnetorheological elastomer (MRE) (Bastola et al, 2020;Snarskii et al, 2021;Wen et al, 2020;Yu et al, 2015) have been identified. In some cases, the use of these materials has led to commercial-scale production by BASF (Munoz et al, 1999), Lord crop (Andrew et al, 2008), Delfi (Iyengar and Foister, 2003, 2004a, 2004b, and Ford (Ginder et al, 1996) company.…”
Section: Introductionmentioning
confidence: 99%